Impactos de la contaminación sonora generada por discotecas en la salud y bienestar del entorno urbano circundante en Punchana, Loreto, 2024 - Acosta Rodriguez, Lady Stefany (2025)
Noise pollution is a growing issue in urban environments, particularly in areas near nighttime recreational activities. In Punchana, Loreto, the noise generated by nightclubs negatively affects the quality of life of nearby populations. This study aimed to assess the effects of noise pollution from nightclubs on the health and well-being of the surrounding population. International and national research has demonstrated the relationship between noise exposure and its adverse effects on physical health and mental state, including stress disorders, cardiovascular diseases, and sleep disturbances. The results indicate that nighttime noise levels exceed permissible limits, reaching up to 82 dB in Fragata, 68 dB in Copacabana, and 63 dB in Chelodromo. Reports highlighted negative impacts on quality of life and difficulty sleeping. Statistical analysis revealed a positive correlation (r = 0.75) between noise perception and its effects on health. It is concluded that noise pollution from nightclubs significantly impacts the well-being of the population, emphasizing the need for regulation.